Watermelon rind pectin structure influences digestibility and impacts on gut microbiota: a comparative in vitro study - Daniel A. Méndez; Ana Enríquez-Belenguer; Joaquim Calvo-Lerma; María José Fabra; Amparo López-Rubio; María Carmen Collado; Manuel Bernabeu; Antonio Martínez-Abad (Food Research International, 2026)

Evolutionary rewiring of transcriptional networks is temporally associated with a putative 'Shield and Sword' pathogenicity strategy - Víctor Coca-Ruiz; Valmore Henrique Pereira dos Santos; David Benitez-Toledo; José A. Martínez-Olivares; María Jesús Durán-Peña; Isidro G. Collado; Josefina Aleu (Physiological and Molecular Plant Pathology, 2026)

Superovulation with eCG alone or combined with the GnRH analogue buserelin improves transferable embryo production in weaned sows without affecting Day 6 embryo morphological, cellular, and transcriptomic parameters - Adelina Lopez-Jara; Manuela Garcia-Canovas; Henar Gonzalez-Ramiro; Carolina G. Cabrera-Gomez; David Gascon-Collado; Paula Blanco-Cueto; Maria A. Gil; Cristina Cuello; Inmaculada Parrilla; Emilio A. Martinez; Heriberto Rodriguez-Martinez; Cristina A. Martinez-Serrano (Animal Reproduction Science, 2026)

Sialolith in a minor salivary gland of an 8-year-old European domestic shorthair cat: a case report - Javier Collados; Manuel Fuertes-Recuero; Carlos A. Rice; Carolina Naranjo; Cynthia Bell (Veterinary Research Communications, 2026)

Investigating safety aspects of using insect farming to reduce pig and chicken wastes at semi-commercial and lab-scale - L.S. McDowall; A. Collado; R. Clarkson; G. Reiss; K. McDermott (Waste Management, 2026)

Pareto-Based Multi-Objective Calibration of a Hydrological Model Integrating Streamflow and Snow Cover Area - Jose-David Hidalgo-Hidalgo; David Pulido-Velazquez; Antonio-Juan Collados-Lara; A. Arda Şorman; A. Şensoy (Water Resources Management, 2026)
Accurate hydrological modeling in high-mountainous snow-dominated basins is essential for effective water resource management, particularly in climate change-sensitive regions. To better understand the processes that govern hydrological responses, model calibration against multiple variables offers a valuable approach for reducing parameter uncertainty and model equifinality. In data-scarce environments, simple lumped-parameter hydrological models that account for snow accumulation and melting processes are particularly useful. In this study, we used the Témez lumped hydrological model enhanced by the integration of a new semi-distributed snow module to simulate key snow-related processes. We performed a novel sensitivity analysis of the efficiency of the models depending on the adopted multi-objective functions within an automatic procedure to calibrate and validate the models. We evaluated three calibration approaches by varying the weight of the snow cover objective $$\:{w}_{S}$$ . The first procedure consisted of a single-objective calibration against streamflow alone. The other procedures applied multi-objective calibration against streamflow and snow cover, which differed in the performance metric used for the snow component: Nash-Sutcliffe efficiency and Kling-Gupta efficiency. The results demonstrated that incorporating snow cover data into the calibration process improved snow cover simulation without significantly compromising streamflow efficiency, except when the streamflow weight $$\:{w}_{Q}$$ was reduced to zero. Notably, the KGE-based approach yielded a better-defined Pareto front with a more robust snow cover efficiency and reduced bias. Our findings also revealed that snow-related parameters were highly sensitive to the inclusion of snow cover data. Key parameters exhibited substantial changes, with a reduction in variability of approximately 30%.

A Detailed Characterization of the Whistle Repertoire of Fraser's Dolphins ( Lagenodelphis hosei ) From the Lesser Antilles - Laura J. May‐Collado; Maia Austin; Lucas Bernier; Jeffrey Bernus; Beth Brady; Lauren Viegas; Eric A. Ramos (Marine Mammal Science, 2026)
Fraser's dolphin ( Lagenodelphis hosei ) remains poorly studied due to its elusive behavior, rarity, and preference for deep offshore habitats. While dolphins use frequency‐modulated whistles for communication, detailed acoustic descriptions exist for only a few species. This study provides the first comprehensive characterization of Fraser's dolphin whistle acoustic structure and repertoire, based on recordings from eight groups (15–300 individuals) collected during boat‐based surveys at three sites in the Lesser Antilles. A total of 2999 whistles were analyzed for acoustic structure, with 1802 contours and a subsample of 728 whistles (weighted by group size) categorized using Beluga and ARTwarp to estimate repertoire size and composition. Whistles exhibited a broader frequency range (1.12–31.40 kHz) than previously reported. Acoustic overlap across sites supports the hypothesis of a proposed single population in the region. The repertoire was comprised of 298 whistle types, predominantly upsweeps and sine contours. Whistle type richness ( q = 0) did not plateau, indicating incomplete sampling of rare types, whereas Shannon ( q = 1) and Simpson ( q = 2) diversity did plateau, suggesting that the most produced whistle types were well represented in this study. These findings offer a detailed baseline of Fraser's dolphin whistle repertoire and contribute to the development of species‐specific detectors for passive acoustic monitoring, as well as future research on geographic variation, social communication, and responses to environmental and anthropogenic changes.

Incidence and risk factors of surgical site infection in dogs undergoing laparoscopy ovariectomy. Multicentric prospective cohort study - M. Fuertes-Recuero; J. Espinel Rupérez; M. Abal-Flores; G. Gonzalez-Matellano; M. Gardoqui-Arias; A. Rubio Guivernau; A. Fraile-Fernandez; D. Carrero Escolar; C. Sánchez-Collado; D. Calzado-Barranco; J.C. Fontanillas-Pérez; G. Ortiz-Diez (The Veterinary Journal, 2025)

Cryptic Heleobia populations (Caenogastropoda: Cochliopidae) from northern Chilean highlands: evidence of high-altitude speciation - Gonzalo A. Collado (Organisms Diversity & Evolution, 2025)

What strategies would sheep farmers implement to respond to climate change? A cross-national comparison of sheep farming systems in the Mediterranean - D. Martin-Collado; A. Tenza-Peral; I. Casasús; M. Joy; F. Stark; A. Lurette; A. Mohamed-Brahmi; M. Ameur; A. Aboulnaga; M. Elshafie; S. Lobón (Small Ruminant Research, 2025)

Selenium removal from oil refinery wastewater using nanoscale zero-valent iron particles (nZVI) with and without electrochemical peroxidation - M. E. Hansen; S. Collado; C. Gutiérrez; R. Ortiz; P. Lazo; A. Lazo; H. K. Hansen (International Journal of Environmental Science and Technology, 2025)

Under threat: Land use change, distribution and conservation of poorly-known endemic microsnails from the coast of Chile - Gonzalo A. Collado; Juan Francisco Araya; Viviana Castillo; Nicolás I. Villalobos (Anthropocene, 2025)

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Dual-Curing MWCNT nanocomposites for Energy-Efficient electroactive shape memory and In-Situ processing - I. Collado; A. Vázquez-López; A. Jiménez-Suárez; S.G. Prolongo (Chemical Engineering Journal, 2025)

Invasive New and Old World freshwater species in isolated springs of the Atacama Desert: implications for native species - Gonzalo A. Collado; Rebeca Carballo; Nicolás Villalobos; Francisco Gómez; Viviana Castillo; Álvaro Alonso (New Zealand Journal of Marine and Freshwater Research, 2025)
Invasive species can significantly alter invaded ecosystems. In this study, we report the presence of two invasive species, the poeciliid fish Poecilia reticulata and the gastropod Melanoides tuberculata , in three isolated springs from the coast of the Atacama Desert in Antofagasta city, northern Chile. Both species were identified through diagnostic morphological features and phylogenetic analysis. This is the first confirmed record of P. reticulata in natural ecosystems of Chile. The finding of M. tuberculata represents the first record of the species in the Antofagasta Region, and the third in the country. Considering the well‐documented adverse effects of both species on invaded ecosystems and their high potential for spread, we recommend the prompt implementation of mitigation measures. These should focus on the direct mechanical removal of these species, given the relatively straightforward sampling process and the relatively small size of the springs. Such measures would significantly contribute to the preservation of native species, particularly those categorized as vulnerable.

Presence of a supernumerary root of the right mandibular second molar in a Staffordshire terrier: a case report - Javier Collados; Manuel Fuertes-Recuero; Carlos A. Rice (Veterinary Research Communications, 2025)

Unveiling the intruders: molecular and morphological identification of three invasive freshwater species in a southern Chilean lake - Gonzalo A. Collado; Rebeca Carballo; Álvaro Alonso (Limnology, 2025)

Effects of the invasive aquatic snail Potamopyrgus antipodarum (Gray, 1853) on ecosystem properties and services - Álvaro Alonso; Gonzalo A. Collado; Claudia Gérard; Edward P. Levri; Rodrigo B. Salvador; Pilar Castro-Díez (Hydrobiologia, 2025)
Ecosystems provide benefits to humans, including provisioning, regulating, and cultural services. However, invasive species can threaten ecosystem well-functioning and services provided. One invasive species with such potential is the New Zealand mud snail (NZMS) Potamopyrgus antipodarum . The aims of this study are focused on the quantitative review of (1) the NZMS impacts on ecosystem properties and their direct links with ecosystem services, and (2) the ecosystem services that can be affected by the NZMS. The high density reached by this species in most of the invaded ecosystems and its highly competitive ability affect ecosystem structure and functioning. However, some facilitation processes on native species may result in an improvement of some services. The NZMS tends to positively affect cultural services (88% positive cases) but negatively to provisioning services (77% of cases). Regarding, regulating and maintenance services, the proportions of positive and negative effects were similar (45% vs 36%, respectively). Therefore, the NZMS is a species with numerous negative impacts on ecosystem services. However, ecosystem services related to health (e.g., dilution effect against parasites) and research (e.g., biomonitoring) are cultural services that the NZMS can improve. No economic assessment of the impacts of the NZMS is available in the literature.

Open-mouth jaw locking in a 5-year-old Persian cat: a case report - Manuel Fuertes-Recuero; Javier Collados; Felipe de Vicente; Carlos A. Rice; Raquel Salgüero (Veterinary Research Communications, 2024)

Long sediment-laden algal turf likely impairs coral recovery on Florida’s coral reefs - A. Duran; K. E. Speare; C. Fuchs; T. C. Adam; L. Palma; M. W. Miller; L. Collado-Vides; A. R. Harborne; D. E. Burkepile (Coral Reefs, 2024)

Assessing the temporal isolation barrier between two closely related species of the genus Fissurella off the southwestern coast of South America - Gonzalo A. Collado; Selva L. Luna; Donald I. Brown (Invertebrate Reproduction & Development, 2024)

“Alstroemeria maxima (Alstroemeriaceae, Alstroemerieae), a hidden giant” revealed through integrative taxonomy - Nicolás I. Villalobos; Carlos M. Baeza; Víctor L. Finot; Óscar Toro-Núñez; Eduardo Ruiz-Ponce; Koji Takayama; Hiroshi Noda; Gonzalo A. Collado; Freddy Mora-Poblete (Brazilian Journal of Botany, 2024)

Magnetic amyloid-based biocatalyst for the hydrolysis of urea - A. de Athayde Moncorvo Collado; S.B. Socías; F. González-Lizárraga; D. Ploper; E. Vera Pingitore; R.N. Chehín; S. Chaves (Food Chemistry, 2024)

Transcending the nature-society dichotomy: A dialogue between the Sumak Kawsay and the epistemology of complexity - A. Malo Larrea; M. Ambrosi de la Cadena; J. Collado Ruano; L. Gallardo Fierro (Ecological Economics, 2024)

Membrane fractioning of pre-treated waste activated sludge for the recovery of valuable biocompounds - Daniel Núñez; Paula Oulego; Mahdi Nikbakht Fini; Jens Muff; Sergio Collado; Francisco A. Riera; Mario Díaz (Journal of Water Process Engineering, 2023)

High similarities in dorsal fin ratios of common bottlenose dolphins ( Tursiops truncatus ) in the Caribbean Sea - Carlos A. Niño‐Torres; Jose A. Olvera‐Gómez; Eric Ramos; Delma N. Castelblanco‐Martínez; María P. Blanco‐Parra; Laura J. May‐Collado; Rita Sellares (Marine Mammal Science, 2023)
Dorsal fins, one of the most notable dolphin's physical features, play important kinematic and hydrodynamic roles and are related to physiological and environmental adaptation processes. Differences in dorsal fin shape have been recently associated with geographic variation, habitat specialization between ecotypes, and ontogenetic factors. We studied dorsal fin variation across several common bottlenose dolphin populations in the Caribbean. A total of 252 dorsal fin photographs from eight coastal regions in the Caribbean were selected for analysis. Dolphin dorsal fin proportions were compared among regions and compared with data previously collected from Holbox, Mexico. Dorsal fin models were constructed for each region. We found that across the Caribbean, coastal bottlenose dolphins exhibit low variation in dorsal fin shape, with the most common dorsal fin pattern having low and triangular shapes, two traits that greatly contrast with the oceanic ecotype. Also, significant differences in overall dorsal fin proportions found among some adjacent groups support the hypothesis that subgroups could be present even within extremely short geographical distances ‐ as has been previously documented. The results of this study can be implemented in population monitoring efforts worldwide, as it uses free software and provides a step‐by‐step guideline to analyze the data.

Species movements within biogeographic regions: exploring the distribution of transplanted mollusc species in South America - Gustavo Darrigran; Ignacio Agudo-Padrón; Pedro Baez; Carlos Belz; Franz Cardoso; Gonzalo A. Collado; Modesto Correoso; María Gabriela Cuezzo; Cristina Damborenea; Alejandra A. Fabres; Monica A. Fernandez; Suzete R. Gomes; et al. (Biological Invasions, 2023)

Socio-environmental impacts of non-native and transplanted aquatic mollusc species in South America: What do we really know? - Alvar Carranza; Ignacio Agudo-Padrón; Gonzalo A. Collado; Cristina Damborenea; Alejandra Fabres; Diego E. Gutiérrez Gregoric; Cesar Lodeiros; Sandra Ludwig; Guido Pastorino; Pablo Penchaszadeh; Rodrigo B. Salvador; Paula Spotorno; et al. (Hydrobiologia, 2023)

A universal approach to alpha-cellulose extraction for radiocarbon analysis of 14C-free to post-bomb ages - Guaciara M. Santos; Anita S.Y. Komatsu; Jazmine M. Renteria; Arno F.N. Brandes; Christopher A. Leong; Silvana Collado-Fabbri; Ricardo De Pol-Holz (Quaternary Geochronology, 2023)

Assessing biodiversity within the range of Heleobia chimbaensis (Caenogastropoda: Cochliopidae) on the Atacama Desert coast - Gonzalo A. Collado; Carmen G. Fuentealba; Néstor J. Cazzaniga; Moisés A. Valladares (Systematics and Biodiversity, 2020)

Multiple late‐Pleistocene colonisation events of the Antarctic pearlwort Colobanthus quitensis (Caryophyllaceae) reveal the recent arrival of native Antarctic vascular flora - Elisabeth M. Biersma; Cristian Torres‐Díaz; Marco A. Molina‐Montenegro; Kevin. K. Newsham; Marcela A. Vidal; Gonzalo A. Collado; Ian S. Acuña‐Rodríguez; Gabriel I. Ballesteros; Christian C. Figueroa; William P. Goodall‐Copestake; Marcelo A. Leppe; Marely Cuba‐Díaz; et al. (Journal of Biogeography, 2020)
Aim Antarctica's remote and extreme terrestrial environments are inhabited by only two species of native vascular plants. We assessed genetic connectivity amongst Antarctic and South American populations of one of these species, Colobanthus quitensis , to determine its origin and age in Antarctica. Location Maritime Antarctic, sub‐Antarctic islands, South America. Taxon Antarctic pearlwort Colobanthus quitensis (Caryophyllaceae). Methods Four chloroplast markers and one nuclear marker were sequenced from 270 samples from a latitudinal transect spanning 21–68° S. Phylogeographic, population genetic and molecular dating analyses were used to assess the demographic history of C. quitensis and the age of the species in Antarctica. Results Maritime Antarctic populations consisted of two different haplotype clusters, occupying the northern and southern Maritime Antarctic. Molecular dating analyses suggested C. quitensis to be a young ( Main conclusions. The Maritime Antarctic populations likely derived from two independent, late‐Pleistocene dispersal events. Both clusters shared haplotypes with sub‐Antarctic South Georgia, suggesting higher connectivity across the Southern Ocean than previously thought. The overall findings of multiple colonization events by a vascular plant species to Antarctica, and the recent timing of these events, are of significance with respect to future colonizations of the Antarctic Peninsula by vascular plants, particularly with predicted increases in ice‐free land in this area. This study fills a significant gap in our knowledge of the age of the contemporary Antarctic terrestrial biota. Adding to previous inferences on the other Antarctic vascular plant species (the grass Deschampsia antarctica ), we suggest that both angiosperm species are likely to have arrived on a recent (late‐Pleistocene) time‐scale. While most major groups of Antarctic terrestrial biota include examples of much longer‐term Antarctic persistence, the vascular flora stands out as the first identified terrestrial group that appears to be of recent origin.

Novel microsatellite markers for an endangered freshwater snail, Heleobia atacamensis (Caenogastropoda: Cochliopidae), from the Atacama Saltpan - Alejandra A. Fabres; Moisés A. Valladares; Paola A. Sáez; Gonzalo A. Collado; Luis Pastenes; Marco A. Méndez (Molluscan Research, 2020)

Deconstructing the landscape of fear in stable multi‐species societies - A. E. Martínez; E. Parra; L. F. Collado; V. T. Vredenburg (Ecology, 2017)
Animal distributions are influenced by variation in predation risk in space, which has been described as the “landscape of fear.” Many studies suggest animals also reduce predation risk by eavesdropping on heterospecific alarm calls, allowing them to occupy otherwise risky habitats. One unexplored area of study is understanding how different species’ alarms vary in quality, and how this variation is distributed in the landscape. We tested this phenomenon in a unique system of avian mixed species flocks in Amazonian rainforests: flock mates (eavesdropping species) strongly associate with alarm‐calling antshrikes (genus Thamnomanes ), which act as sentinel species. Up to 70 species join these flocks, presumably following antshrike behavioral cues. Since flocks in this region of the Amazon are exclusively led by a single antshrike species, this provides a unique natural system to compare differences in sentinel quality between flocks. We simulated predation threat by flying three species of live trained raptors (predators) towards flocks to compare sentinel probability to (1) produce alarm calls, and (2) encode information about magnitude and type of threat within such alarm calls. Our field experiments show significant differences in the probability of different sentinel species to produce alarm calls and distinguish predators. This variation may have important fitness consequences and shape the “landscape of fear” for eavesdropping species.

Impact of universal access to hepatitis C therapy on HIV-infected patients: implementation of the Spanish national hepatitis C strategy - A. Rivero-Juarez; L. F. Lopez-Cortes; M. Castaño; D. Merino; M. Marquez; M. Mancebo; F. Cuenca-Lopez; P. Jimenez-Aguilar; I. Lopez-Montesinos; S. Lopez-Cardenas; A. Collado; M. A. Lopez-Ruz; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Unraveling cryptic invasion of a freshwater snail in Chile based on molecular and morphological data - Gonzalo A. Collado (Biodiversity and Conservation, 2017)

Trichothecenes and aspinolides produced by Trichoderma arundinaceum regulate expression of Botrytis cinerea genes involved in virulence and growth - Mónica G. Malmierca; Inmaculada Izquierdo‐Bueno; Susan P. McCormick; Rosa E. Cardoza; Nancy J. Alexander; Javier Barua; Laura Lindo; Pedro A. Casquero; Isidro G. Collado; Enrique Monte; Santiago Gutiérrez (Environmental Microbiology, 2016)
Summary Trichoderma arundinaceum (Ta37) and Botrytis cinerea (B05.10) produce the sesquiterpenoids harzianum A (HA) and botrydial (BOT), respectively. TaΔTri5, an HA non‐producer mutant, produces high levels of the polyketide compounds aspinolides (Asp) B and C. We analyzed the role of HA and Asp in the B. cinerea ‐ T. arundinaceum interaction, including changes in BOT production as well as transcriptomic changes of BcBOT genes involved in BOT biosynthesis, and also of genes associated with virulence and ergosterol biosynthesis. We found that exogenously added HA up‐regulated the expression of the BcBOT and all the virulence genes analyzed when B. cinerea was grown alone. However, a decrease in the amount of BOT and a down‐regulation of BcBOT gene expression was observed in the interaction zone of B05.10‐Ta37 dual cultures, compared to TaΔTri5. Thus, the confrontation with T. arundinaceum results in an up‐regulation of most of the B. cinerea genes involved in virulence yet the presence of T. arundinaceum secondary metabolites, HA and AspC, act separately and together to down‐regulate the B. cinerea genes analyzed. The present work emphasizes the existence of a chemical cross‐regulation between B. cinerea and T. arundinaceum and contributes to understanding how a biocontrol fungus and its prey interact with each other.

Unravelling cryptic species of freshwater snails (Caenogastropoda, Truncatelloidea) in the Loa River basin, Atacama Desert - Gonzalo A. Collado; Moisés A. Valladares; Marco A. Méndez (Systematics and Biodiversity, 2016)

Understanding the simultaneous biodegradation of thiocyanate and salicylic acid by Paracoccus thiocyanatus and Pseudomonas putida - R. G. Combarros; S. Collado; A. Laca; M. Díaz (International Journal of Environmental Science and Technology, 2016)

Dimension of chronic hepatitis C virus in HIV-infected patients in the interferon-free era: an overview from south Spain - A. Rivero-Juarez; A. Gutierrez-Valencia; M. Castaño; D. Merino; K. Neukam; M. J. Ríos-Villegas; M. A. Lopez-Ruz; P. Jiménez-Aguilar; M. Marquez; A. Collado; A. Gomez-Vidal; J. Hernandez-Quero; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Efficacy of and risk of bleeding during pegylated interferon plus ribavirin treatment in HIV/HCV-coinfected patients with pretreatment thrombocytopenia - J. A. Mira; K. Neukam; L. F. López-Cortés; A. Rivero-Juárez; F. Téllez; J. A. Girón-González; I. de los Santos-Gil; G. Ojeda-Burgos; D. Merino; M. J. Ríos-Villegas; A. Collado; A. Torres-Cornejo; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Comparative genome analysis of Bacillus spp. and its relationship with bioactive nonribosomal peptide production - A. Hamdache; R. Azarken; A. Lamarti; J. Aleu; I. G. Collado (Phytochemistry Reviews, 2013)

Allometry, biomass, and chemical content of Novel African Tulip Tree (Spathodea campanulata) Forests in Puerto Rico - Ariel E. Lugo; Oscar J. Abelleira; Alexander Collado; Christian A. Viera; Cynthia Santiago; Diego O. Vélez; Emilio Soto; Giovanni Amaro; Graciela Charón; Héctor Colón; Jennifer Santana; José L. Morales; et al. (New Forests, 2011)

Monophyly, candidate species and vicariance in Biomphalaria snails (Mollusca: Planorbidae) from the Southern Andean Altiplano - Gonzalo A. Collado; Irma Vila; Marco A. Méndez (Zoologica Scripta, 2011)
Collado, G. A., Vila, I. & Méndez, M. A. (2011). Monophyly, candidate species and vicariance in Biomphalaria snails (Mollusca: Planorbidae) from the Southern Andean Altiplano. — Zoologica Scripta , 40 , 613–622. The landscape of the Neotropical southern Andean Altiplano is characterized by a succession of closed basins originated from the Miocene to the Holocene. In this region, the number of species and phylogenetic relationships among freshwater snails of the genus Biomphalaria are uncertain. Here we obtained sequences of the mitochondrial gene cytochrome oxidase subunit I from 17 Altiplano populations, including topotypes of three nominal species, which were analyzed together with published sequences of the genus using different methods of phylogenetic reconstruction and a species of Helisoma as outgroup. The Altiplano populations conform a monophyletic group whose sister group is the Neotropical species Biomphalaria peregrina. Within this clade we recovered four main lineages well supported and congruent with geographical distributions. One clade includes topotypes restricted exclusively to the Ascotán basin, the type locality of the nominal species Biomphalaria crequii . A second clade includes sequences that correspond to topotypes restricted to the Isluga and Carcote basins, the type localities of the nominal species Biomphalaria aymara and Biomphalaria costata , respectively. Two monophyletic groups clustered snails restricted to several aquatic systems within the Caquena and Lauca basins, which may represent candidate species. The branching pattern of the sequences suggests that in the diversification of these snails, events of vicariance inferred in the Pleistocene have predominated over dispersal phenomena.

Four years of vertebrate monitoring on an upper Amazonian river - Nigel C. A. Pitman; Darren Norris; Jerry Martínez Gonzalez; Eriberto Torres; Fernando Pinto; Hernán Collado; Wilberth Concha; Raúl Thupa; Edwin Quispe; Jorge Pérez; Juan Carlos Flores del Castillo (Biodiversity and Conservation, 2011)

Neuroprotective effect of carvedilol and melatonin on 3-nitropropionic acid-induced neurotoxicity in neuroblastoma - I. Tasset; C. Espínola; F. J. Medina; M. Feijóo; C. Ruiz; E. Moreno; M. M. Gómez; J. A. Collado; C. Muñoz; J. Muntané; P. Montilla; I. Túnez (Journal of Physiology and Biochemistry, 2009)

Mapping quantitative trait loci for growth responses to exogenously applied stress induced hormones in wheat - A. M. Castro; M. S. Tacaliti; D. Giménez; E. Tocho; O. Dobrovolskaya; A. Vasicek; M. Collado; J. W. Snape; A. Börner (Euphytica, 2008)

Impact of mining activities on soils in a semi-arid environment: Sierra Almagrera district, SE Spain - Andres Navarro; Diego Collado; Montserrat Carbonell; Juan A. Sanchez (Environmental Geochemistry and Health, 2004)

Usefulness of Sputum Culture for Diagnosis of Bacterial Pneumonia in HIV-Infected Patients - Cordero E.; Pachón J.; Rivero A.; Girón-González J.; Gómez-Mateos J.; Merino M.; Torres-Tortosa M.; González-Serrano M.; Aliaga L.; Collado A.; Hernández-Quero J.; Barrera A.; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

The Putative Role of Botrydial and Related Metabolites in the Infection Mechanism of Botrytis cinerea - A. J. Colmenares; J. Aleu; R. Durán-Patrón; I. G. Collado; R. Hernández-Galán (Journal of Chemical Ecology, 2002)